Gut Microbes Regulate Innate Immunity and Epilepsy - Zhang, Linhai; Li, Shuang; Tai, Zhenzhen; Yu, Changyin; Xu, Zucai (Frontiers in Neuroscience, 2022)
Epilepsy is a common chronic brain disease. There are many clinical methods to control epileptic seizures, such as anti-seizure medications (ASMs) or surgical removal of epileptogenic lesions. However, the pathophysiology of epilepsy is still unknown, making it difficult to control or prevent it. The host's immune system monitors gut microbes, interacts with microbes through pattern recognition receptors such as Toll-like receptors (TLRs) and NOD-like receptors (NLRs) expressed by innate immune cells, and activates immune responses in the body to kill pathogens and balance the relationship between microbes and host. In addition, inflammatory responses induced by the innate immune system are seen in animal models of epilepsy and temporal lobe epilepsy brain tissue to combat pathogens or injuries. This review summarizes the potential relationship between gut microbes, innate immunity, and epilepsy based on recent research to provide more hints for researchers to explore this field further.